Developing Cybersecurity Workforce: Introducing CyberSec Labs for Industry Standard Cybersecurity Training - Kose, Yasin; Ozer, Murat; Bastug, Mehmet; Varlioglu, Said; Basibuyuk, Oguzhan; Ponnakanti, Hari Priya (Proceedings - 2021 International Conference on Computational Science and Computational Intelligence, CSCI 2021, 2021)
In recent years, widespread internet usage, increasing numbers of IoT devices, and vast data on social media have increased cyber attack vectors. Parallel to this trend, the demand for the cyber security workforce has augmented; however, employers could not fill these positions due to the shortage in the field. This anomaly, in turn, has placed companies in a vulnerable situation by being exposed to an increased level of cyber security threats/incidents. Relevant authorities underscore the importance of a comprehensive cybersecurity workforce framework to overcome this problem. Given this context, this study offers a CyberSec Labs framework to improve the skills of potential cybersecurity actors. The framework extensively benefits from hands-on exercises like cloud computing and networking, OSINT, data-driven cybersecurity approach, vulnerability and penetration test analysis, and volatility analysis. The overall goal of this open-source material is to prepare students for their future cybersecurity roles, which contributes to overcoming the shortage of skilled human capital in the cybersecurity field.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Cybersecurity Lab; Cybersecurity Training; Cybersecurity Workforce